STRANGER THAN FICTION: THE AUTHOR-HERO RELATIONSHIP IN THE AESTHETICS OF THE CINEMATOGRAPHIC DISCOURSE - Stafuzza, Grenissa Bonvino (Laboratório Editorial FCL-UNESP, 2012)
The aim of this article is to construct an analytical and discursive study concerning the relationship author-hero in the feature film Stranger than fiction (2005). We start the discussion considering some theoretical propositions formalized by Bakhtin/Voloshinov (2009), such as  language conceived in its  social nature, the enunciation in respect to the communication inter-locutors and the building of the relationship  sign-ideology in language (in this respect, the cinematographic) to anticipate some questions involving the relationship author-hero, founded by Bakhtin (1992). Then, we transcribe some filmic statements selected to the analysis, noting how the relationship between the author, Karen Eiffel, and the hero, Harold Crick, is established by a dialogical exchange supported by a dynamic relation with the verbal-visual enunciation of Stranger than fiction which organizes the cinematographic work as a whole.